TUGAS POKOK DAN FUNGSI KANTOR CAMAT KAYAN HILIR KABUPATEN SINTANG - Syamsudin, Martinus (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2024)
The problem studied in this research is the implementation of the main duties and functions of the Kayan Hilir sub-district head, Sintang Regency. The aim to be achieved in this research is to find out, describe and analyze the implementation of the main duties and functions of the sub-district head with this research method using descriptive research. The subjects in the sub-district head, section heads, research techniques used in data collection were observation, interviews and documentation studies with data analysis using qualitative descriptive analysis methods. The results of this research show that the Coordination Function has been carried out in accordance with the theory of internal coordination, namely coordination from the leadership in order to coordinate the implementation of the main tasks of the District Government. The coaching function of the Kayan Hilir Subdistrict Head has been carried out by providing guidance to the apparatus in carrying out work. The Community Service function, which is the implementation of the village government's main task in serving the community, has been carried out.